Controles sobre o Judiciário geram governança e eficiência? Estudo sobre o CNJ e a Justiça Estadual - Oliveira, Leonel Gois Lima (2015)
The objective of this thesis is to investigate the acts of the juidicial control agency in the Judiciary Branch, focused on dimension ‘Administrative Judicial Performance’. This thesis aims to complement Taylor’s model (2008) by adding CNJ as a variant on Courts performance improvement, since it implements managerial tools on courts and generates political and institutional impacts. The study is based on the political and organizational context of Judiciary to provide a supplement to the current understanding of the performance measurement mechanisms. CNJ impacts were analyzed from seven aspects of Judicial Reform process: 1. Standardization of structures; 2. Centralized manag ement systems; 3. Standardization of procedures; 4. Centralization of budget; 5. Financing of legal units; 6. Disciplinary proceedings against irregularities and bad conduct of judges; 7 . Meritocratic criteria and promotion of judges. The data was collected through structured interviews with CNJ’s ex and current advisers and it considers the ten years’ time of CNJ existence (2004-2013), providing a longitudinal perspective. Thematic or Categorical Analysis was chosen as the main form of content analysis technique. Data was segmented by questions, previous categories and categories established later. It was found that CNJ has a direct effect on Administrative Judicial Performance by: i) using management tools that allow the courts to improve the internal organization and raise the level of governance maturity; ii) moralizing and supervising courts through frequent inspections from National Justice Comptroller, that aim to solve irregularities and remove misconducting judges. The evidences also identified indirect impacts: i) CNJ is a Judiciary’s actions coordinator, articulating better relations with Executive and Legislative Branches representatives and getting more budgetary and financial resources to courts; ii) CNJ improves Judiciary autonomy by recognizing courts’ management efforts and sharing best practices among other courts, with impacts on infrastructure and the performance improvements. Increased control promoted by CNJ strengthened gove rnance and efficiency of the courts, but with loss of autonomy at first. Furthermore, subsequently, generated a profile change in the indications of his advisers in an attempt to weaken the control and increasing autonomy of the courts.